2021
DOI: 10.1177/02692163211001719
|View full text |Cite
|
Sign up to set email alerts
|

‘Living in parallel worlds’ – bereaved parents’ experience of family life when a parent with dependent children is at end of life from cancer: A qualitative study

Abstract: Background: When a parent of dependent children (<18 years old) is at end of life from cancer, this has a profound impact on the family. Children less prepared for the death of a parent are more susceptive to poorer psychosocial adjustment in later life. There is a lack of understanding from the literature surrounding what support parents require, and how they navigate this end of life experience. Aim: To explore bereaved parents’ experience and needs for families when a parent is at end of life from cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 36 publications
0
36
0
2
Order By: Relevance
“…Strain on family life due to work or financial pressures, combined with parental grief, may also mean that is harder for parents to provide the emotional support that young people need, whilst perceived distress or vulnerability in the parents may also stop children from talking about their feelings (8,12,13). Pre-pandemic and pandemic research has also demonstrated maladaptive tendencies amongst adults to try to protect children by not talking about the death pre-and postbereavement (8,(14)(15)(16)(17), uncertainty about how best to prepare children for the death (15,18), and difficulties maintaining parenting roles in the midst of their own grief and disruption (4). The difficulties of bereaved children and young people in managing and expressing their feelings has also been documented (4).…”
Section: Introductionmentioning
confidence: 99%
“…Strain on family life due to work or financial pressures, combined with parental grief, may also mean that is harder for parents to provide the emotional support that young people need, whilst perceived distress or vulnerability in the parents may also stop children from talking about their feelings (8,12,13). Pre-pandemic and pandemic research has also demonstrated maladaptive tendencies amongst adults to try to protect children by not talking about the death pre-and postbereavement (8,(14)(15)(16)(17), uncertainty about how best to prepare children for the death (15,18), and difficulties maintaining parenting roles in the midst of their own grief and disruption (4). The difficulties of bereaved children and young people in managing and expressing their feelings has also been documented (4).…”
Section: Introductionmentioning
confidence: 99%
“…A child may not be prepared if death occurs quickly or unexpectedly and this may affect subsequent psychological adjustment [16]. Recent research has shown that clinicians can play an important role in supporting and preparing the family when a parent is facing death due to cancer [39,40]. Training healthcare professionals to facilitate open communication between parents and children, especially when the prognosis is poor, may help mitigate the severe impact of loss [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that clinicians can play an important role in supporting and preparing the family when a parent is facing death due to cancer [39,40]. Training healthcare professionals to facilitate open communication between parents and children, especially when the prognosis is poor, may help mitigate the severe impact of loss [40,41]. We also found that children bereaved during adolescence had the highest risk, but conclusions must be made with caution, as this may reflect efforts that have been made in Denmark to restrict prescription of psychotropic medication in children under 12 years [42].…”
Section: Discussionmentioning
confidence: 99%
“…Bereaved families have reflected it would have been helpful if HSCPs had started a conversation with them on how best to tell the children someone close to them was going to die. 2 This would require HSCP to: (1) understand the long-term benefits of effective communication for children's psychological well-being and family functioning; and (2) identify children within a patient's family and social network. HSCPs should ask their patients and/ or the relatives 'do you have important relationships with children?'.…”
Section: Open Accessmentioning
confidence: 99%